Case Report: An atypical presentation of acute zonal occult outer retinopathy (AZOOR) - Bhakhri, Raman (Canadian Journal of Optometry, 2023)
Abstract: Acute Zonal Occult Outer Retinopathy (AZOOR) is a rare inflammatory condition that is considered part of the white dot disease spectrum and may be due to viral or autoimmune causes. Signs and symptoms can include scotomas, persistent photopsia’s, and potential vision loss. The condition typically presents unilaterally in young Caucasian females with fundus signs being minimal or absent leading to a delayed or missed diagnosis. This report details an atypical presentation of AZOOR with bilateral appearance with focal retinal deposits in a middle-aged black female. A comprehensive review of the condition is presented including pathophysiology, treatment, and multimodal imaging results.